Method for resource utilization of electrolytic manganese residues
Electrolytic manganese slag based concrete is prepared by mixing electrolytic manganese slag with alkali trigger for baking and ball milling, and then mixing it with fly ash, nanomaterials, cement and water, which solves the waste of resources and environmental pressure caused by electrolytic manganese slag treatment. The problem has achieved efficient resource utilization and improved mechanical performance.
Patent Information
- Application Number
- CN202411661801.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
Traditional treatments of electrolytic manganese slag lead to waste of resources and environmental pressures, and their storage and emissions may cause harm to human health and ecological balance.
Electrolytic manganese slag is prepared by mixing electrolytic manganese slag with alkali exciter for calcination and ball milling, and then activated with fly ash, nanomaterials, cement and water to prepare electrolytic manganese slag-based concrete to achieve resource utilization of electrolytic manganese slag.
This method optimizes the internal structure of manganese slag and fly ash through dual activation processes, improves the mechanical properties of electrolytic manganese slag-based concrete, and realizes efficient resource utilization and environmental sustainability.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resource utilization of industrial solid waste, and in particular to a method for resource utilization of electrolytic manganese slag. Background Art
[0002] Electrolytic manganese slag is a waste material produced in the process of electrolytic manganese metal. Its main components are calcium sulfate dihydrate, silicon dioxide, ammonium sulfate and trace amounts of heavy metal pollutants. These components are toxic and may cause allergies, respiratory and digestive tract inflammation and other problems after inhalation or contact with the skin. In addition, if the heavy metal pollutants in electrolytic manganese slag are discharged into the environment, they will cause serious damage to the ecosystem. The traditional methods for treating electrolytic manganese slag mainly include damming and landfilling. However, the storage of electrolytic manganese slag requires a large amount of land. Long-term accumulation not only causes waste of resources, but also increases environmental pressure; and the storage and arbitrary discharge of electrolytic manganese slag will destroy the surrounding ecological balance and affect the living environment of animals and plants; when anti-seepage measures are not in place, it may also enter the human body through water and soil, causing harm to human health, affecting the quality of life of local residents and social stability.
[0003] Therefore, providing a method for resource utilization of electrolytic manganese slag is of great significance for alleviating resource waste and environmental pressure, and maintaining human health and ecological balance. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems existing in the prior art and provide a method for resource utilization of electrolytic manganese slag.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for resource utilization of electrolytic manganese slag, comprising the following steps:
[0007] (1) mixing electrolytic manganese slag and an alkaline activator, and performing roasting. After the roasting, the mixture is ball-milled to obtain activated electrolytic manganese slag;
[0008] (2) mixing fly ash and an alkali activator, and calcining the mixture. After the calcination, the mixture is ball-milled to obtain activated fly ash;
[0009] (3) mixing the activated electrolytic manganese slag, activated fly ash, nanomaterials, cement and water to obtain electrolytic manganese slag-based concrete, thereby completing the resource utilization of the electrolytic manganese slag;
[0010] There is no order of precedence between step (1) and step (2).
[0011] Preferably, the alkaline activator in step (1) comprises calcium hydroxide or triethanolamine;
[0012] The mass ratio of the electrolytic manganese slag to the alkaline activator is 80-100:10-20.
[0013] Preferably, the calcination temperature in step (1) is 590-610° C., and the calcination time is 1.8-2.2 h.
[0014] Preferably, the rotation speed of the ball mill in step (1) is 200 to 800 r / min, and the ball milling time is 2.5 to 3.5 h.
[0015] Preferably, the alkaline activator in step (2) comprises one or more of calcium hydroxide, sodium hydroxide, sodium carbonate and sodium silicate;
[0016] The mass ratio of the fly ash to the alkali activator is 200-220:10-20.
[0017] Preferably, the calcination temperature in step (2) is 590-610° C., and the calcination time is 1.8-2.2 h.
[0018] Preferably, the rotation speed of the ball mill in step (2) is 200 to 800 r / min, and the ball milling time is 2.5 to 3.5 h.
[0019] Preferably, the particle size of the activated electrolytic manganese slag in step (3) is 1 to 16 mm; the mass ratio of the activated electrolytic manganese slag with a particle size greater than or equal to 5 mm and less than or equal to 16 mm to the activated electrolytic manganese slag with a particle size greater than or equal to 1 mm and less than 5 mm is 3.2 to 3.5:1.9 to 2.2.
[0020] Preferably, the nanomaterial in step (3) comprises nano calcium carbonate or nano silicon dioxide.
[0021] Preferably, in step (3), the mass ratio of the activated electrolytic manganese slag, activated fly ash, nanomaterial, cement and water is 30-35:65-70:2-3.5:5-9:2-6.
[0022] The beneficial effects of the present invention are:
[0023] The present invention provides a method for resource utilization of electrolytic manganese slag, comprising the following steps: mixing electrolytic manganese slag and an alkali activator, roasting, and after the roasting, ball milling to obtain activated electrolytic manganese slag; mixing fly ash and an alkali activator, roasting, and after the roasting, ball milling to obtain activated fly ash; mixing the activated electrolytic manganese slag, the activated fly ash, nanomaterials, cement and water to obtain electrolytic manganese slag-based concrete, thereby completing the resource utilization of electrolytic manganese slag. The present invention performs a dual activation process on electrolytic manganese slag and fly ash, and the alkali activation and mechanical activation cooperate with each other, which greatly optimizes the internal structure of manganese slag and fly ash, fully stimulates the silicon and aluminum activity of manganese slag and fly ash, and then improves the mechanical properties of the obtained electrolytic manganese slag-based concrete. In addition, the added nanomaterials can also play a role in filling the internal pores of the concrete material, which can make the internal structure more compact, thereby further improving the mechanical properties of the electrolytic manganese slag-based concrete. The method of the invention is simple and environmentally friendly, and realizes the resource utilization of electrolytic manganese slag while also realizing the efficient utilization of fly ash, thereby preparing an electrolytic manganese slag-based concrete with excellent performance. DETAILED DESCRIPTION
[0024] The present invention provides a method for resource utilization of electrolytic manganese slag, comprising the following steps:
[0025] (1) mixing electrolytic manganese slag and an alkaline activator, and performing roasting. After the roasting, the mixture is ball-milled to obtain activated electrolytic manganese slag;
[0026] (2) mixing fly ash and an alkali activator, and calcining the mixture. After the calcination, the mixture is ball-milled to obtain activated fly ash;
[0027] (3) mixing the activated electrolytic manganese slag, activated fly ash, nanomaterials, cement and water to obtain electrolytic manganese slag-based concrete, thereby completing the resource utilization of the electrolytic manganese slag;
[0028] There is no order of precedence between step (1) and step (2).
[0029] In the present invention, the electrolytic manganese slag in step (1) is preferably dried before mixing with the alkaline activator; the drying temperature is preferably 60-70°C, more preferably 62-68°C, and more preferably 65°C; the drying time is preferably 22-26h, more preferably 23-25h, and more preferably 24h.
[0030] In the present invention, the alkaline activator in step (1) preferably includes calcium hydroxide or triethanolamine.
[0031] In the present invention, the mass ratio of the electrolytic manganese slag to the alkaline activator is preferably 80-100:10-20, more preferably 85-95:12-18, and more preferably 90-92:15-16.
[0032] In the present invention, the calcination temperature in step (1) is preferably 590-610°C, more preferably 595-605°C, and more preferably 600-602°C; the calcination time is preferably 1.8-2.2h, more preferably 1.9-2.1h, and more preferably 1.95-2h.
[0033] In the present invention, after the calcination in step (1) is completed, the mixture is naturally cooled to room temperature and then ball milled.
[0034] In the present invention, the rotation speed of the ball mill in step (1) is preferably 200-800 r / min, more preferably 300-700 r / min, more preferably 500-600 r / min; the ball milling time is preferably 2.5-3.5 h, more preferably 2.7-3.3 h, more preferably 2.8-3 h.
[0035] In the present invention, the fly ash in step (2) is preferably dried before mixing with the alkali activator; the drying temperature is preferably 60-70°C, more preferably 62-68°C, and more preferably 65°C; the drying time is preferably 22-26h, more preferably 23-25h, and more preferably 24h.
[0036] In the present invention, the alkaline activator in step (2) preferably includes one or more of calcium hydroxide, sodium hydroxide, sodium carbonate and sodium silicate.
[0037] In the present invention, the mass ratio of the fly ash to the alkali activator is preferably 200-220:10-20, more preferably 205-215:12-18, and more preferably 210-212:15-16.
[0038] In the present invention, the calcination temperature in step (2) is preferably 590-610°C, more preferably 595-605°C, and more preferably 600-602°C; the calcination time is preferably 1.8-2.2h, more preferably 1.9-2.1h, and more preferably 1.95-2h.
[0039] In the present invention, after the calcination in step (2) is completed, the mixture is naturally cooled to room temperature and then ball milled.
[0040] In the present invention, the rotation speed of the ball mill in step (2) is preferably 200-800 r / min, more preferably 300-700 r / min, more preferably 500-600 r / min; the ball milling time is preferably 2.5-3.5 h, more preferably 2.7-3.3 h, more preferably 2.8-3 h.
[0041] In the present invention, the particle size of the activated electrolytic manganese slag in step (3) is preferably 1-16 mm; the mass ratio of the activated electrolytic manganese slag with a particle size greater than or equal to 5 mm and less than or equal to 16 mm to the activated electrolytic manganese slag with a particle size greater than or equal to 1 mm and less than 5 mm is preferably 3.2-3.5:1.9-2.2, further preferably 3.3-3.4:2.0-2.1, and more preferably 3.35:2.05.
[0042] In the present invention, the nanomaterial in step (3) preferably includes nano calcium carbonate or nano silicon dioxide.
[0043] In the present invention, the mass ratio of the activated electrolytic manganese slag, activated fly ash, nanomaterial, cement and water in step (3) is preferably 30-35:65-70:2-3.5:5-9:2-6, further preferably 31-34:66-69:2.5-3:6-8:3-5, and more preferably 32-33:67-68:2.7-2.8:7-7.5:4-4.5.
[0044] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0045] Example 1
[0046] The electrolytic manganese slag was dried at 65°C for 23 hours, the dried electrolytic manganese slag was mixed with calcium hydroxide (the mass ratio of electrolytic manganese slag to calcium hydroxide was 90:15), and calcined at 600°C for 2 hours. After the calcination, the mixture was naturally cooled to room temperature, and ball-milled at a speed of 500 r / min for 3 hours to obtain activated electrolytic manganese slag;
[0047] The fly ash was dried at 65°C for 23 hours, the dried fly ash was mixed with calcium hydroxide (the mass ratio of fly ash to calcium hydroxide was 210:15), and calcined at 600°C for 1.9 hours. After the calcination, it was naturally cooled to room temperature, and ball milled at a speed of 600 r / min for 2.8 hours to obtain activated fly ash;
[0048] The activated electrolytic manganese slag (with a particle size of 1 to 16 mm, wherein the mass ratio of the activated electrolytic manganese slag with a particle size of 5 mm or more and 16 mm or more and the activated electrolytic manganese slag with a particle size of 1 mm or more and 5 mm or less is 3.35:2.05), activated fly ash, nanomaterials (nano-calcium carbonate), cement and water are mixed, and the mass ratio of the activated electrolytic manganese slag, the activated fly ash, the nanomaterials, the cement and the water is 32:68:2:7:4.5, to obtain electrolytic manganese slag-based concrete, thereby completing the resource utilization of the electrolytic manganese slag.
[0049] Example 2
[0050] The electrolytic manganese slag was dried at 60°C for 24 hours, the dried electrolytic manganese slag was mixed with calcium hydroxide (the mass ratio of electrolytic manganese slag to calcium hydroxide was 85:12), and calcined at 590°C for 2.2 hours. After the calcination, it was naturally cooled to room temperature, and ball milled at a speed of 700 r / min for 2.7 hours to obtain the activated electrolytic manganese slag;
[0051] The fly ash was dried at 60°C for 24 hours, the dried fly ash was mixed with calcium hydroxide (the mass ratio of fly ash to calcium hydroxide was 200:10), and calcined at 590°C for 2.2 hours. After the calcination, it was naturally cooled to room temperature, and ball milled at a speed of 700 r / min for 2.7 hours to obtain activated fly ash;
[0052] The activated electrolytic manganese slag (with a particle size of 1 to 16 mm, wherein the mass ratio of the activated electrolytic manganese slag with a particle size of 5 mm or more and 16 mm or more and the activated electrolytic manganese slag with a particle size of 1 mm or more and 5 mm or less is 3.3:2.0), activated fly ash, nanomaterials (nano-silicon dioxide), cement and water are mixed, and the mass ratio of the activated electrolytic manganese slag, the activated fly ash, the nanomaterials, the cement and the water is 31:69:3:8:5, to obtain electrolytic manganese slag-based concrete, thereby completing the resource utilization of the electrolytic manganese slag.
[0053] Example 3
[0054] The electrolytic manganese slag was dried at 70°C for 22 hours, the dried electrolytic manganese slag was mixed with calcium hydroxide (the mass ratio of electrolytic manganese slag to calcium hydroxide was 100:16), and calcined at 610°C for 1.8 hours. After the calcination, it was naturally cooled to room temperature, and ball milled at a speed of 300 r / min for 3.3 hours to obtain the activated electrolytic manganese slag;
[0055] The fly ash was dried at 70°C for 22 hours, the dried fly ash was mixed with calcium hydroxide (the mass ratio of fly ash to calcium hydroxide was 200:12), and calcined at 610°C for 1.8 hours. After the calcination, it was naturally cooled to room temperature, and ball milled at a speed of 300 r / min for 3.3 hours to obtain activated fly ash;
[0056] The activated electrolytic manganese slag (with a particle size of 1 to 16 mm, wherein the mass ratio of the activated electrolytic manganese slag with a particle size of 5 mm or more and 16 mm or more and the activated electrolytic manganese slag with a particle size of 1 mm or more and 5 mm or less is 3.5:2.2), activated fly ash, nanomaterials (nano calcium carbonate), cement and water are mixed, and the mass ratio of the activated electrolytic manganese slag, the activated fly ash, the nanomaterials, the cement and the water is 35:70:2.5:9:6, to obtain electrolytic manganese slag-based concrete, thereby completing the resource utilization of the electrolytic manganese slag.
[0057] Comparative Example 1
[0058] The other conditions in Example 1 were kept unchanged, and the electrolytic manganese slag was dried at 65° C. for 23 h and then directly ball-milled at a speed of 500 r / min for 3 h; finally, electrolytic manganese slag-based concrete was prepared, completing the resource utilization of the electrolytic manganese slag.
[0059] Comparative Example 2
[0060] The other conditions in Example 1 are controlled to remain unchanged, and the process of ball milling the electrolytic manganese slag is omitted; finally, the electrolytic manganese slag-based concrete is prepared, and the resource utilization of the electrolytic manganese slag is completed.
[0061] Comparative Example 3
[0062] The other conditions in Example 1 are controlled to remain unchanged, the process of activating fly ash is omitted, and the fly ash is directly mixed with the activated electrolytic manganese slag, nanomaterials, cement and water; finally, electrolytic manganese slag-based concrete is prepared, completing the resource utilization of electrolytic manganese slag.
[0063] Comparative Example 4
[0064] The other conditions in Example 1 are controlled to remain unchanged, and no nanomaterial is added; finally, electrolytic manganese slag-based concrete is prepared, and the resource utilization of electrolytic manganese slag is completed.
[0065] The electrolytic manganese slag-based concrete prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were respectively placed in molds (with a size of 40 mm×40 mm×160 mm), and then placed on a cement mortar specimen forming and compacting table for compaction. After 24 hours, the concrete was demolded and placed in a curing box with a temperature of 20° C. and a relative humidity of 90% for 28 days of curing to obtain electrolytic manganese slag-based concrete test blocks. According to GB / T17671-1999, the compressive performance of the concrete was tested to obtain the performance test results of different electrolytic manganese slag-based concrete test blocks, as shown in Table 1.
[0066] Table 1 Performance test results of different electrolytic manganese slag-based concrete
[0067] Case 28-day compressive strength (MPa) Example 1 29.0 Example 2 29.3 Example 3 28.9 Comparative Example 1 25.8 Comparative Example 2 26.3 Comparative Example 3 23.1 Comparative Example 4 24.7
[0068] It can be seen from the above embodiments that the present invention provides a method for resource utilization of electrolytic manganese slag, comprising the following steps: mixing electrolytic manganese slag and an alkali activator, roasting, and after the roasting, ball milling to obtain activated electrolytic manganese slag; mixing fly ash and an alkali activator, roasting, and after the roasting, ball milling to obtain activated fly ash; mixing the activated electrolytic manganese slag, the activated fly ash, nanomaterials, cement and water to obtain electrolytic manganese slag-based concrete, and completing the resource utilization of electrolytic manganese slag. The present invention performs a dual activation process on electrolytic manganese slag and fly ash, and the alkali activation and mechanical activation cooperate with each other, which greatly optimizes the internal structure of manganese slag and fly ash, fully stimulates the silicon and aluminum activity of manganese slag and fly ash, and then improves the mechanical properties of the obtained electrolytic manganese slag-based concrete. In addition, the added nanomaterials can also play a role in filling the internal pores of the concrete material, which can make the internal structure more compact, thereby further improving the mechanical properties of the electrolytic manganese slag-based concrete. The method of the invention is simple and environmentally friendly, and realizes the resource utilization of electrolytic manganese slag while also realizing the efficient utilization of fly ash, thereby preparing an electrolytic manganese slag-based concrete with excellent performance.
[0069] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for resource utilization of electrolytic manganese slag, characterized in that: It includes the following steps: (1) mixing electrolytic manganese slag and an alkaline activator, and performing roasting. After the roasting, the mixture is ball-milled to obtain activated electrolytic manganese slag; (2) mixing fly ash and an alkali activator, and calcining the mixture. After the calcination, the mixture is ball-milled to obtain activated fly ash; (3) mixing the activated electrolytic manganese slag, activated fly ash, nanomaterials, cement and water to obtain electrolytic manganese slag-based concrete, thereby completing the resource utilization of the electrolytic manganese slag; There is no order of precedence between step (1) and step (2).
2. The method for resource utilization of electrolytic manganese slag according to claim 1, characterized in that: The alkaline activator in step (1) comprises calcium hydroxide or triethanolamine; The mass ratio of the electrolytic manganese slag to the alkaline activator is 80-100:10-20.
3. The method for resource utilization of electrolytic manganese slag according to claim 1 or 2, characterized in that: The calcination temperature in step (1) is 590-610° C., and the calcination time is 1.8-2.2 hours.
4. The method for resource utilization of electrolytic manganese slag according to claim 3, characterized in that: The rotation speed of the ball mill in step (1) is 200 to 800 r / min, and the ball milling time is 2.5 to 3.5 h.
5. The method for resource utilization of electrolytic manganese slag according to claim 4, characterized in that: The alkaline activator in step (2) includes one or more of calcium hydroxide, sodium hydroxide, sodium carbonate and sodium silicate; The mass ratio of the fly ash to the alkali activator is 200-220:10-20.
6. The method for resource utilization of electrolytic manganese slag according to claim 5, characterized in that: The calcination temperature in step (2) is 590-610° C., and the calcination time is 1.8-2.2 h.
7. The method for resource utilization of electrolytic manganese slag according to claim 6, characterized in that: The rotation speed of the ball mill in step (2) is 200 to 800 r / min, and the ball milling time is 2.5 to 3.5 h.
8. The method for resource utilization of electrolytic manganese slag according to claim 7, characterized in that: The particle size of the activated electrolytic manganese slag in step (3) is 1 to 16 mm; the mass ratio of the activated electrolytic manganese slag with a particle size greater than or equal to 5 mm and less than or equal to 16 mm to the activated electrolytic manganese slag with a particle size greater than or equal to 1 mm and less than 5 mm is 3.2 to 3.5:1.9 to 2.
2.
9. The method for resource utilization of electrolytic manganese slag according to claim 8, characterized in that: The nano material in step (3) includes nano calcium carbonate or nano silicon dioxide.
10. The method for resource utilization of electrolytic manganese slag according to claim 9, characterized in that: In step (3), the mass ratio of the activated electrolytic manganese slag, activated fly ash, nanomaterial, cement and water is 30-35:65-70:2-3.5:5-9:2-6.